2007
DOI: 10.1016/j.jnoncrysol.2007.05.134
|View full text |Cite
|
Sign up to set email alerts
|

Lowest-energy structures of 13-atom binary clusters: Do icosahedral clusters exist in binary liquid alloys?

Abstract: Although the existence of 13-atom icosahedral clusters in one-component close-packed undercooled liquids was predicted more than half a century ago by Frank, the existence of such icosahedral clusters is less clear in liquid alloys. We study the lowest-energy structures of 13-atom A x B 13-x Lennard-Jones binary clusters using the modified space-fixed genetic algorithm and the artificial Lennard-Jones potential designed by Kob and Andersen. Curiously, the lowest-energy structures are non-icosahedral for almost… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…8 Computer modelling calculations were used to design new molecules of desired performance by inserting gold nanoparticles and aromatic fragments in the oligo-(dibenzyl sulphide) molecules using either full search or GA. 227 Similar studies are also reported elsewhere. [228][229][230][231][232] Colour recipe prediction problem keeping spectrophotometric and colorimetric colour matching as targets with the limitation of colorant numbers is also available in the literature using GAs. 233 A multiobjective GA framework considering the mechanical performance and the electrical conductivity properties is adopted to optimise the input parameters for a Cu-Cr-Zr-Mg lead frame alloy where a supervised artificial NN is considered to model the non-linear relationship among the parameters of aging treatment, hardness and conductivity properties.…”
Section: Other Applicationsmentioning
confidence: 99%
“…8 Computer modelling calculations were used to design new molecules of desired performance by inserting gold nanoparticles and aromatic fragments in the oligo-(dibenzyl sulphide) molecules using either full search or GA. 227 Similar studies are also reported elsewhere. [228][229][230][231][232] Colour recipe prediction problem keeping spectrophotometric and colorimetric colour matching as targets with the limitation of colorant numbers is also available in the literature using GAs. 233 A multiobjective GA framework considering the mechanical performance and the electrical conductivity properties is adopted to optimise the input parameters for a Cu-Cr-Zr-Mg lead frame alloy where a supervised artificial NN is considered to model the non-linear relationship among the parameters of aging treatment, hardness and conductivity properties.…”
Section: Other Applicationsmentioning
confidence: 99%
“…Even in binary glass-forming systems, clear evidence of the influence of ordering in the liquid state has been reported [3][4][5][11][12][13][14][15][16][17]. For example, the marginal glass-forming ability in the Al-RE (aluminum rare-earth) systems has been associated with ordering in the liquid phase [18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…While considerable work has been done on homogeneous clusters, considerably less effort has been devoted to the details of nonhomogeneous clusters. Binary clusterscontaining two types of particlehave received some attention, , but the general level of understanding is still well behind that of the homogeneous clusters, since the parameter space is so large. However, since fullerenes can be generated in a wide variety of sizes, this seems to be a natural area in which mixed clusters with components of different sizes can be investigated experimentally.…”
Section: Introductionmentioning
confidence: 99%